PELATIHAN PEMBUKUAN KEUANGAN DI YAYASAN SUMATRA VOLUNTEER DI JORONG BALAI LABUAH BAWAH KABUPATEN TANAH DATAR - Winny Alna Marlina; Nefy Puteri Novani; Handoko Handoko (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2022)
The Sumatra Volunteer Foundation was established in 2014. One of the Foundation's programs is to provide free English language education for children, youth and the community. The Foundation's location is in Jorong Balai Labuah Bawah, Lima Kaum, Tanah Datar. Sumatra straws is part of the Sumatra Volunteer Foundation which produces straws from bamboo. The sales system is still conventional in the form of word of mouth starting from friends to friends, then campus students and assisted by student alumni and internship students at the Sumatra Volunteer Foundation. Financial Recording is still mixed with personal finance and there are no financial reports such as sales data, purchase data, inventory data. The purpose of this activity is to develop a product craft business at the Sumatra Volunteer Foundation to downstream products from bamboo so that the Foundation is financially independent. Methods and stages of implementing activities in the form of training and demonstrations of making financial reports to partners directly, making websites and procuring goods. The activity was held on October 9, 2021 with the theme of simple bookkeeping training. In the activities of the presenters transferring knowledge about financial statements, then the owner of the Foundation immediately practiced using software. The results of service activities in the form of financial software provided to the Foundation to facilitate financial bookkeeping. Financial software contains profit and loss data, cash flow, income data, inventory data. With financial training, the Foundation can separate personal financial reports from the Foundation so that they can find out financial transactions at the Foundation. The conclusion of the activity is beneficial for the Foundation and future activities in the form of managing the legality of the business.